2007
DOI: 10.1042/cs20070321
|View full text |Cite
|
Sign up to set email alerts
|

Does compensatory nitric oxide and angiotensin II receptor activity reduce arterial stiffness in early-stage insulin resistance?

Abstract: Increased arterial stiffness is influenced by both functional and structural properties of the vessel wall, including changes in content of smooth muscle, elastin and collagen, reduced endothelial production of NO and increased release of endothelin-1 or AngII (angiotensin II). The RAS (renin-angiotensin) system is likely to be central to increases in arterial stiffness, since the changes in arterial structure observed with enhanced AngII activity are similar to the same pathophysiological changes that contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…16,17 Several mechanisms may explain the 'accelerated ageing' of the aortic wall compared with the carotid wall in patients with MetS. MetS is characterized by activation of the renin-angiotensin system, 18 an important humoral factor involved in regulating the turnover of extracellular matrix proteins and a strong regulator of matrix metalloproteinase and tissue inhibitor of metalloproteinases, 19 as well as of cytokines released by adipose tissue. 20 Glycation of matrix proteins also exerts an adverse effect on the structure and function of large arteries.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Several mechanisms may explain the 'accelerated ageing' of the aortic wall compared with the carotid wall in patients with MetS. MetS is characterized by activation of the renin-angiotensin system, 18 an important humoral factor involved in regulating the turnover of extracellular matrix proteins and a strong regulator of matrix metalloproteinase and tissue inhibitor of metalloproteinases, 19 as well as of cytokines released by adipose tissue. 20 Glycation of matrix proteins also exerts an adverse effect on the structure and function of large arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II type 1 receptor also binds directly to endothelial NO synthase and inhibits its activity, leading to a decrease in NO production. [45,46] At the same time, increased aldosterone levels activate endothelial mineralocorticoid receptors and ultimately lead to increased sodium channel activity, which can lead to several adverse consequences, including remodeling of the cortical actin skeleton, increased vascular permeability, and inflammation. [47] In vitro animal studies have shown that enhanced endothelial cell mineralocorticoid activity is associated with vascular fibrosis and stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the combined vasodilator effects of increased basal NO levels and increased AT2R expression in INSR subjects are likely to be signifi cant contributors to the observed increased arterial compliance in the early stages of INSR states, and may represent an early response to vascular damage, 58 some of which is induced by increased AT1R expression. AT1R blockade may therefore be a useful treatment for INSR states, with its triple effect of blocking harmful AT1R-mediated vascular effects, increased AT2R expression, 59 and increased AII formation with unopposed AT2R activation.…”
mentioning
confidence: 99%